The throwing shoulder: A review of functional anatomy, biomechanics, injury prevention and rehabilitation strategies - Appleby, B. (Journal of Australian Strength and Conditioning, 2016)
Consistent performance of high velocity, accurate overhead throwing is a remarkable achievement by the shoulder joint. The action of throwing is a full body action, where the goal is the successful transfer of lower body generated force through to the hand to maximise ball velocity. The ability of the shoulder girdle to perform this action, given the magnitude of mobility at the glenohumeral joint is accomplished by many structures. The shoulder joint has tremendous range of motion at the expense of structural stability. Glenohumeral stability is achieved by a range of static and dynamic structures. The capability for the shoulder to move through range either under load or with high velocity is due to an intricate coordination of muscles acting on the scapula and humerus, delicately altering muscle lengths and forces to achieve glenohumeral stability. This coordination is controlled by constant neural information provided by several specialised structures within the muscles, tendons and ligaments of the shoulder girdle. Overhead throwing places enormous demands on the shoulder joint through range, velocity and force. Overhead throwers adapt to repetitive throwing with several changes to the static and dynamic structures. However, some of these protective and performance enhancing alterations to the structure, or function of the links in the scapulothoracic and glenohumeral chains, can still lead to injury. Successful rehabilitation and injury prevention of such a highly coordinated, highly mobile joint performing repetitive actions of considerable force and velocity, such as throwing, requires knowledge of anatomical adaptations and function to be successful. Injury prevention requires attention to balance of muscular strength, flexibility and endurance of scapular stabilisers and the rotator cuff. The monitoring of throwing technique and volume, particularly in developing athletes is critical. The first step in successful rehabilitation is accurate diagnosis. Shoulder pain can result from unsuccessful accommodation of scapulothoracic structures. The restoration of scapular stability is a key component of shoulder rehabilitation. Biomechanical intervention to the throwing action may be required to reduce the likelihood of re-injury.